The Pengembangan Modul Pelatihan Bagi Orang Tua Dalam Pendampingan Belajar Siswa Dari Rumah Pascapandemi Covid-19 - Batmanlusy, Dian Erilya; Mawardi; Wasitohadi (Universitas Kristen Satya Wacana, 2024)
This study aims to describe the role of parents in accompanying students during and after the COVID-19 pandemic at SMP Negeri 13 Ambon and SMP Negeri 20 Ambon. It explores the challenges, disadvantages, and strengths of parental involvement in home-based learning during and after the pandemic, and presents a training module for parents to assist students learning post-pandemic. This research employs a research and development (RnD) approach with a qualitative descriptive method, focusing on product creation. Data were collected through document studies, observations, and in-depth interviews, and validated using source and technique triangulation. Data analysis followed the Miles and Huberman Model. The findings are: During the COVID-19 pandemic, parents at SMP Negeri 13 Ambon and SMP Negeri 20 Ambon provided some assistance for home-based learning, but it was not fully effective due to varying conditions and parents' limited understanding of the online learning process, compounded by some parents' technological illiteracy. Post-pandemic, parental assistance returned to normal, with some parents struggling to motivate their children, who preferred in-person learning and social interactions at school. The primary obstacles faced by parents included poor internet connectivity, high data costs, and frequent power outages, while the strengths included increased attention, encouragement, guidance, and direct control over children's learning at home. A training module for parents was developed, comprising a module book with guides for learning activities that can be implemented by teachers, parents, and students.